DESIGN AND PERFORMANCE EVALUATION OF A HIGH-VOLTAGE DC GENERATOR USING A COCKCROFT-WALTON MULTIPLIER - Turahyo Turahyo; Noviarianto Noviarianto (PT. Jurnal Center Indonesia Publisher, 2026)
This paper presents the design and performance evaluation of a high-voltage direct current (DC) generator based on the Cockcroft–Walton (CW) voltage multiplier for laboratory-scale applications in electrical engineering. Conventional high-voltage generation methods often involve bulky transformers and complex circuitry, making them less suitable for compact and cost-effective laboratory use. To address these limitations, a modular CW-based system is proposed, integrating a high-frequency input source with an optimized diode-capacitor ladder network. The proposed system is designed to achieve high DC voltage output in the kilovolt range while maintaining acceptable levels of ripple and efficiency. Experimental results show that the system can achieve up to 86% of the theoretical output voltage under no-load conditions, with an efficiency of around 70.8%. Furthermore, the ripple voltage of the generated output voltage is very small, demonstrating stable performance suitable for laboratory applications. The proposed design offers a compact, cost-effective, and reliable solution for high-voltage DC generation, making it highly suitable for educational and low-power applications.